Impact of Brain Metastases on Treatment Patterns and Outcomes With First-Line Durvalumab Plus Platinum-Etoposide in Extensive-Stage SCLC (CASPIAN): A Brief Report - Chen, Yuanbin; Paz-Ares, Luis; Reinmuth, Niels; Garassino, Marina Chiara; Statsenko, Galina; Hochmair, Maximilian J; Özgüroğlu, Mustafa; Verderame, Francesco; Havel, Libor; Losonczy, György; Conev, Nikolay V; Hotta, Katsuyuki; et al. (JTO clinical and research reports, 2022)
INTRODUCTION: In the phase 3 study involving the use of durvalumab with or without tremelimumab in combination with platinum-based chemotherapy in untreated extensive-stage SCLC (CASPIAN study), first-line durvalumab plus platinum-etoposide (EP) significantly improved overall survival (OS) versus EP alone (p = 0.0047). We report exploratory subgroup analyses of treatment patterns and outcomes according to the presence of baseline brain or central nervous system metastases. METHODS: Patients (WHO performance status 0 or 1), including those with asymptomatic or treated-and-stable brain metastases, were randomized to four cycles of durvalumab plus EP followed by maintenance durvalumab until progression or up to six cycles of EP and optional prophylactic cranial irradiation. Prespecified analyses of OS and progression-free survival (PFS) in subgroups with or without brain metastases used unstratified-Cox proportional hazards models. The data cutoff was on January 27, 2020. RESULTS: At baseline, 28 out of 268 patients (10.4%) in the durvalumab plus EP arm and 27 out of 269 patients (10.0%) in the EP arm had known brain metastases, of whom 3 of 28 (10.7%) and 4 of 27 (14.8%) had previous brain radiotherapy, respectively. Durvalumab plus EP (versus EP alone) prolonged OS (hazard ratio, 95% confidence interval) in patients with (0.79, 0.44-1.41) or without (0.76, 0.62-0.92) brain metastases, with similar PFS results (0.73, 0.42-1.29 and 0.80, 0.66-0.97, respectively). Among patients without brain metastases, similar proportions in each arm developed new brain lesions as part of their first progression (8.8% and 9.5%), although 8.3% in the EP arm received prophylactic cranial irradiation. Similar proportions in each arm received subsequent brain radiotherapy (20.5% and 21.2%), although more common in patients with than without baseline brain metastases (45.5% and 18.0%). CONCLUSIONS: The OS and PFS benefit with first-line durvalumab plus EP were maintained irrespective of the presence of brain metastases, further supporting its standard-of-care use.
Keywords: CASPIAN; Central nervous system; Extensive-stage SCLC; Immunotherapy; Brain metastases